2019
DOI: 10.1111/tbed.13267
|View full text |Cite
|
Sign up to set email alerts
|

Deathbed choice by ASF‐infected wild boar can help find carcasses

Abstract: African swine fever (ASF) is a fatal disease infectious to wild and domesticated suids. This disease entered the European Union in 2014 and recently reached western Europe, with the first cases observed in Belgium in September 2018. Carcasses of ASF‐infected wild boar play an important role in the spread and persistence of the virus in the environment. Thus, rapidly finding and removing carcasses is a crucial measure for effective ASF control. Using distribution modelling, we investigated whether the fine‐scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…It has been suggested that animals infected with ASF often select deathbeds in cool and moist habitats [48]. Therefore, we included carcass 2wallow in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that animals infected with ASF often select deathbeds in cool and moist habitats [48]. Therefore, we included carcass 2wallow in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to focus on identification and search through localities where carcasses are most likely to be found. The first studies suggested that ASF‐infected wild boars selected deathbeds in cool, moist or/and water‐rich habitats (Morelle, Ježek, Licoppe, & Podgorski, ).…”
Section: Discussionmentioning
confidence: 99%
“…By fitting a mechanistic disease-dynamic model to spatio-temporal disease surveillance data using prior knowledge of wild boar population dynamics, we inferred that 53-66% of ASFV transmission events occurred through the contact of susceptible hosts with dead carcasses. Because wild boar tend not to contact carcasses immediately, but will continue to contact carcasses even during the later stages of decay (Probst et al 2017), increased surveillance and elimination of carcasses could dramatically decrease transmission (Morelle et al 2019). Thus, developing cost-effective methods for carcass detection and retrieval may be critical to reduce transmission rates in wild boar populations (Guinat et al 2017).…”
Section: Discussionmentioning
confidence: 99%